Agresivitas Pajak dan Pengungkapan Corporate Social Responsibility: Komposisi Direksi Sebagai Variabel Moderasi - Saman, Saman; Abdillah, Pujangga; Yahya, Raihan Fahrisal (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2024)
This research aims to understand the impact of tax aggressiveness on Corporate Social Responsibility Disclosure (CSRD) and to test the board of director as a moderating variable that can enhance the influence of tax aggressiveness on CSRD. The study utilizes 462 annual reports of companies from the period 2021–2023 listed on the Indonesia Stock Exchange as a sample for moderated regression analysis (MRA) using STATA software. The findings indicate how tax aggressiveness affects CSRD as determined by the Global Reporting Initiative (GRI). In other words, the higher the tax aggressiveness, the more companies can reduce CSRD. The research also demonstrates that board of director as a moderating variable empirically enhances the influence of tax aggressiveness on CSRD. This study underscores the importance of director board in the development of CSRD strategies and the corporate world's position. Therefore, promoting director board in corporate decision-making will assist governments and key policymakers worldwide in achieving the Sustainable Development Goals (SDGs).